THE IMPLEMENTATION OF LEARN TO SPEAK ENGLISH SOFTWARE AS A MEDIA FOR IMPROVING THE STUDENTS’ SPEAKING SKILL (AN EXPERIMENTAL STUDY AT POLITEKNIK LP3I MAKASSAR) - Trista Udin, Imran (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
The objectives of this research were: to find out whether or not the use of Learn to Speak English software improves the students’ speaking skill. This research employed Quasi Experimental design. The sample consisted of 32 students of third semester of business administration, Politeknik LP3I Makassar in academic year 2019/2020. The data were collected through speaking test for the students’ speaking skill, Data on the students’ speaking skill were analyzed using descriptive and inferential statistics, the results of the research were: The use of Learn to Speak English software in teaching speaking improved the students speaking skill, It can be concluded that the use of Learn to Speak English software is effective to be implemented in improving the students’ speaking skills in terms of fluency and lexical resource.